Auto purchase order system between retailer and distributor - Teguh Andriyanto; Ary Permatadeny Nevita (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Uncertainty of goods inventory often triggers the occurrence of Bullwhip Effect, where there is accumulation of goods on a stage or lack of goods at another stage in the supply chain. Bullwhip Effect is caused by an error in ordering the amount of goods, error in the time of ordering or delivery of goods. The problem can be solved using information sharing. This research utilizing information sharing between two retailers and one distributors used for the ordering process of goods. The process of ordering goods retailers to distributors is done automatically based on sales data retailers. The order quantity is calculated based on the final stock and the maximum stock value of the goods.